Analisis Kemampuan Berpikir Kritis Siswa Kelas VIII SMP Negeri 1 Narmada Dalam Menyelesaikan Soal Cerita Materi Sistem Persamaan Linear Dua Variabel Tahun Ajaran 2021/2022 - Erinda Agustina Ariyani; Baidowi Baidowi; Wahidaturrahmi Wahidaturrahmi; Nurul Hikmah (Pendidikan Matematika FKIP Universitas Mataram, 2022)
This study aims to describe the critical thinking skills of class VIII students at SMP Negeri 1 Narmada in solving story problems based on a two-variable system of linear equations. This type of research is called descriptive qualitative. The instrument used in this study uses the stages of Perkins and Murphy's critical thinking skills, namely (1) clarification, (2) assessment, (3) inference, and (4) strategy. The subjects in this study were from class VIII.8, which consisted of 36 students, then given essay tests and interviews. The test results data were analyzed to determine the categories of students' critical thinking abilities in the high, medium, and low categories. Then interviews were conducted to examine the test results that had been obtained by students in the high, medium, and low categories. The results of this study indicate that 14% of students with high critical thinking skills have not been able to complete the strategy stage. Fifthly percent of students with moderate critical thinking skills have not been able to complete the inference and strategy stages. Thirty-six percent of students with low critical thinking skills have not been able to complete all stages. This shows that students' critical thinking skills in solving story problems on the material of a two-variable linear equation system are in the medium category.